GREAT PEOPLE WHO CONTRIBUTED TO THE ART OF UZBEKISTAN - Azimova , Gulbahor Hazratkul qizi (INTERNATIONAL CONFERENCES, 2023)
This article describes in detail the great people who contributed to the art of Uzbekistan, the first creative period of the sculptor Ilhom Jabbarov, the development of the visual art of Uzbekistan in the historical genre, the outstanding works of the artist Ilhom Jabbarov and Azamat Khatamov.